2021
DOI: 10.1108/k-12-2020-0913
|View full text |Cite
|
Sign up to set email alerts
|

Managing the COVID-19 pandemic: predictors of trust in institutions in Romania

Abstract: PurposeThe paper discusses the predictors of trust in the institutions and people involved in crisis management at the beginning of the COVID-19 pandemic in Romania. Trust in institutions might be a key factor in the way countries affected by the COVID-19 pandemic deal with the crisis as people might be more willing to accept the restrictions and rules imposed if they trust the key institutions and people involved in managing the pandemic. The paper provides recommendations for key stakeholders to increase tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This research's outcomes showed a positive but non-significant association between belief in science and the development of energy-saving habits within the homes of Romanian citizens. The background of the COVID-19 pandemic could have contributed as well to diminishing trust in public authorities, institutions, politics and science overall in Romania due to an ensemble of fake news, conspiracy theories and uncertainty about the future of the country [62], which, in our opinion, provided a weaker role for the variable "belief in science" to exert influence over the dependent variable in our study as well. Based on the personal viewpoint of the authors, it is not unexpected to obtain these results on the background of the confluence of mixed messaging, misinformation and increasing politicization in Romania which created a convenient setting for eroding trust in science [63].…”
Section: Relationship Between Belief In Science and Individuals' Inco...mentioning
confidence: 68%
“…This research's outcomes showed a positive but non-significant association between belief in science and the development of energy-saving habits within the homes of Romanian citizens. The background of the COVID-19 pandemic could have contributed as well to diminishing trust in public authorities, institutions, politics and science overall in Romania due to an ensemble of fake news, conspiracy theories and uncertainty about the future of the country [62], which, in our opinion, provided a weaker role for the variable "belief in science" to exert influence over the dependent variable in our study as well. Based on the personal viewpoint of the authors, it is not unexpected to obtain these results on the background of the confluence of mixed messaging, misinformation and increasing politicization in Romania which created a convenient setting for eroding trust in science [63].…”
Section: Relationship Between Belief In Science and Individuals' Inco...mentioning
confidence: 68%
“…The importance of high-quality data has not diminished as the pandemic has progressed. The public’s confidence in government institutions proved to be a cornerstone of managing the COVID-19 crisis [21] , [22] . Any irregularities, or even the perception of irregularities, in data, can erode public trust in government institutions, especially in the midst of a pandemic where public-health decisions about mitigation efforts need to be evidence-based.…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of using inaccurate data on research, public policy and trust during the pandemic deserves consideration. 9 , 10 Although not all countries have problematic data, many do, and the research community must be mindful of this. It is crucial for the institutions of these countries to improve the accuracy and timeliness of mortality data to enable effective public health responses to future pandemics and health emergencies.…”
Section: Discussionmentioning
confidence: 99%